Citra Destinasi Air Terjun Madakaripura: Analisis Sentimen Wisatawan di Google Review - Lovinda Lusya Florenza; Awaludin Nugraha; Susanti Withaningsih; Reiza D. Dienaputra; Bambang Hermanto; Dina Oktavia (Jurnal Sosial Humaniora, 2025)
This study examines the digital destination image of MadakaripuraWaterfall by analyzing tourist sentiment expressed in Google Reviewposts from January 2024 to November 2025. The research is motivatedby unique governance issues, particularly the period of temporaryclosure declared by the local government while on-site operationscontinued, which triggered diverse tourist responses on digitalplatforms. The analysis was conducted using the Naïve Bayes sentimentclassification algorithm, word cloud visualization, word frequencyanalysis, and thematic analysis.The findings reveal that positive sentiment dominates (69.44%),primarily driven by appreciation for the natural beauty, sceniclandscape, and the unique “eternal rain” phenomenon. Neutralsentiment (8.18%) mainly consists of factual descriptions related toenvironmental conditions, accessibility, and practical visitorinformation. Meanwhile, negative sentiment (22.38%) is largelyinfluenced by governance-related issues, including the forced use of localguides, unclear pricing systems, and uncomfortable interactions withlocal stakeholders. These governance and service-quality issues areidentified as the main threats to the destination’s digital image.The study proposes several strategic recommendations, includingstrengthening community-based tourism (CBT), implementingtransparent and standardized pricing, enhancing capacity building forlocal guides, and optimizing social media–based visitor feedbackmechanisms.